Sustainable development of a coal-mining region: technological and ecological aspects - O. B. Sheveleva; E. V. Slesarenko (Russian Journal of Economics and Law, 2019)
Objective: to consider sustainable development of a region with mining as predominant economic activity through the prism of the relationship between technological and environmental aspects; to determine the impact of technological development of the coal-mining region on its sustainable development.Methods: the methods of statistical observation, summarizing and grouping of statistical observation materials, the method of analogy, as well as analytical and synthetic methods of analysis were used.Results: the level of technological development and environmental safety has a significant impact on almost all spheres of life, especially in the regions where economic growth is based on mining enterprises. In these conditions, it is of particular importance to assess the relationship between the development of the region specializing in mining, and the level of its technological and environmental development. To this end, on the basis of statistical data, the article assesses the state of technical, technological and environmental components of the coal-mining region (by the example of Kemerovo region), determines their role in improving regional competitiveness and ensuring sustainable development. The specific features and problems of coal industry technologization are revealed, the prospects of its development are determined, the experience of foreign countries is considered. It is established that the technical and technological state of the raw materials sector of Kemerovo region is a threat to regional sustainable development and does not contribute to the increase of its competitive advantages. Among the factors constraining the development of the technical and technological sphere and, as a consequence, the increase in environmental safety, are: high technological inertia of mining enterprises, low-efficiency owner, significant dependence on imports of production means, detachment of the state from the processes of withdrawal and redistribution of raw materials rent.Scientific novelty: increasing the technological level of coal industry through the creation and use of safe, environmentally friendly technologies designed to minimize environmental harm is recognized as the basis for sustainable development of a coal-mining region.Practical significance: the main provisions and conclusions can be used in the development of regional scientific, technical and environmental policies and programs of socio-economic development of territories.